Tantangan Dan Perubahan Dalam Sistem Pendidikan: Isu-Isu Persekolahan Kontemporer Dan Upaya Penanganannya - Handoko, Koko; Iqbal, Muhammad (Journal of Sustainable Education, 2024)
Education is the main foundation for individual and societal development, but faces various complex challenges, especially at the school level. Educational strategy issues or learning problems in Indonesia continue to circulate and have not been resolved, even though various solutions continue to be implemented. The main issues in education and schooling, including gaps in access and quality of education, curriculum burden which causes stress on students, teacher welfare, school infrastructure problems, use of technology in education, and involvement of parents and the community. Through literature analysis and secondary data, identify the impact of these issues and offer potential solutions to improve the education system. These findings emphasize the importance of government intervention, curriculum evaluation, improving teacher welfare, investment in infrastructure, increasing access to technology, and involvement of parents and communities to create a more equitable and quality educational environment.